HOW GUIDED SELF-REFLECTION FOR NURSING STUDENT IMPROVE THEIR CRITICAL THINKING IN PRE-CLINIC STAGE - Rona Cahyantari Merduaty; Aulia Addinillah Arum (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Self-reflection proved to be effective in improving clinical performance and strength in formulating clinical opinions of nursing students. However, self-reflection has not been widely used in the practical learning process in the laboratory at the academic stage in Indonesia. This study aimed to examine the effectiveness of self-reflection assignments in improving nursing students' critical thinking skills during practical learning at the academic stage.Methods: The research method used in this study is a single-subject experimental design and used The Holistic Critical Thinking Scoring Rubric (HCTSR) as an instrument for assessing the respondent's self-reflection after performing two procedures taught in the laboratory. There were 12 nursing students, year 3 and 4, who were asked to write self-reflection using the two kind of guidelines and were given feedback after completing the first self-reflection. This study has been declared pass the ethical review according to the KET-201/UN2.F12.D1.2.1/PPM.00.02/2022 issued by the Ethics Committee of  Faculty of Nursing, Universitas Indonesia.Results: Study indicates that 7 for 12 nursing students perform a positive trend during the procedure by improving their HCTSR score each intervention day. In general, the visual analysis displays an increasing trend from the maximum score of 3 (strong critical thinking) in first self-reflection to maximum score of 4 (very strong critical thinking) in last self-reflection.Conclusion: Guided self-reflection assessment and feedback is effective in improving the critical thinking skills of nursing students who are undergoing practical learning at the academic stage. Guiding questions that are concise and contextual to practice in writing self-reflection, specific self-reflection assessment rubrics, and feedback from lecturer should be essential aspect of every nursing learning process, both at the academic and clinical stages.